A leucine aminopeptidase is involved in kinetoplast DNA segregation in Trypanosoma brucei - Peña-Diaz, Priscila; Vancová, Marie; Resl, Christian; Field, Mark C; Lukeš, Julius (PLoS pathogens, 2017)
The kinetoplast (k), the uniquely packaged mitochondrial DNA of trypanosomatid protists is formed by a catenated network of minicircles and maxicircles that divide and segregate once each cell cycle. Although many proteins involved in kDNA replication and segregation are now known, several key steps in the replication mechanism remain uncharacterized at the molecular level, one of which is the nabelschnur or umbilicus, a prominent structure which in the mammalian parasite Trypanosoma brucei connects the daughter kDNA networks prior to their segregation. Here we characterize an M17 family leucyl aminopeptidase metalloprotease, termed TbLAP1, which specifically localizes to the kDNA disk and the nabelschur and represents the first described protein found in this structure. We show that TbLAP1 is required for correct segregation of kDNA, with knockdown resulting in delayed cytokinesis and ectopic expression leading to kDNA loss and decreased cell proliferation. We propose that TbLAP1 is required for efficient kDNA division and specifically participates in the separation of daughter kDNA networks.
Keywords: DNA, Protozoan; DNA Replication; DNA, Mitochondrial; DNA, Kinetoplast; replikace DNA; buněčný cyklus; Cell Cycle; Protozoan Proteins; protozoální DNA; mitochondrie; leucylaminopeptidasa; Mitochondria; Leucyl Aminopeptidase; zvířata; mitochondriální DNA; Animals; kinetoplastová DNA; protozoální proteiny; Trypanosoma brucei brucei